Market power and the matching of trade credit terms - Fabbri, Daniele (Policy research working paper, 2008)
"This paper studies the decision of firms to extend trade credit to customers and its relation with their financing decisions. The authors use a novel firm-level database of Chinese SMEs with unique information on market power in both output and input markets and on the amount, terms, and payment history of trade credit simultaneously extended to customers (accounts receivable) and received from suppliers (accounts payable). The analysis shows that suppliers with relatively weaker market power are more likely to extend trade credit and have a larger share of goods sold on credit. Examination of the importance of financial constraints reveals that access to bank financing and profitability are not significantly related to trade credit supply. Rather, firms that receive trade credit from their own suppliers are more likely to extend trade credit to their customers, and to "match maturity" between the contract terms of payables and receivables. This matching practice is more likely used when firms face strong competition in the product market (relative to their customers), and enjoy strong market power in the input market (relative to their suppliers). These results highlight the importance of supply chain financing for market competition and risk management in credit constrained firms. "--World Bank web site